G521(P) An evaluation of non-medical prescribing in a children's hospice service. (27th April 2016) - Crooks, HF; Porter, C; Cowling, K; Leishman, R; Reid, F; Boutcher, PA; Carragher, PJ
Abstract : Background: Extensive changes to legislation in the last 15 years have led to a rapid expansion of the role of non-medical prescribers (NMPs). There appears to be a paucity of information evaluating the role that NMPs can play in paediatric palliative care settings. This study examines the role of NMPs in a children's hospice service. Aims: The primary objective of this evaluation was to determine if non-medical prescribing has reduced remote prescribing episodes, enhanced individuals' professional practice and supported medical sustainability within a children's hospice service. Methods: A questionnaire was distributed to nursing and medical staff employed by the children's hospice service to examine their attitudes and opinions of non-medical prescribing. Six months' of prescribing data was collected by all four actively prescribing NMPs within the organisation. This data was compared with data from one year previously when the organisation had only one newly qualified NMP in place. Results: The questionnaire demonstrates a general feeling amongst the nursing and medical teams that non-medical prescribing has led to a positive impact on the children and families, and enabled more timely access to medicines. There was a significant increase in the proportion of prescribing that Schedule 2–5 controlled drugs (CDs) represented (2% in the initial evaluation compared to 13.5% in the 2015 evaluation). This may represent the increased role that NMPs are playing in symptom management and anticipatory prescribing towards end of life. The ages of the children and young people for whom prescriptions were issued by NMPs were analysed (Figure 3 ). Conclusion: NMPs are having a significant impact in a children's hospice service in terms of improving the care of children and young people and enhancing individuals' own professional practice. Further research should focus on children's and families' experiences of non-medical prescribing in the children's hospice setting.